Night work and postpartum depression: a national register-based cohort study - Hammer, Paula; Hageman, Ida; Garde, Anne; Begtrup, Luise; Flachs, Esben; Hansen, Johnni; Hansen, Åse; Hougaard, Karin; Kolstad, Henrik; Larsen, Ann; Pinborg, Anja; Specht, Ina; et al. (Scandinavian Journal of Work, Environment & Health, 2019)
' ' OBJECTIVE ': 'We aimed to investigate the association of night work during pregnancy with the risk of severe postpartum depression (PPD). ' ' METHODS ': 'We performed a nationwide register-based cohort study of workers in all Danish public hospitals. Daily information on working hours was retrieved from the Danish Working Hour Database from January 2007 to December 2015. Pregnancies, covariates and outcome were identified from national registries for births and hospital contacts. We performed logistic regression of the risk of severe PPD in relation to the number and duration of night shifts, spells of consecutive night shifts, and short shift intervals during the first 32 pregnancy weeks. Analyses were adjusted for age, body mass index, socioeconomic status, parity, sickness absence three months prior to pregnancy, and prior diagnosis of severe depression. ' ' RESULTS ': 'The study cohort comprised 25 009 singleton pregnancies from 19 382 workers. The majority were nurses or physicians. Overall, we did not observe an increased risk of PPD for any of the dimensions of night work analyzed. We found, however, an increased risk of PPD (adjusted odds ratio 2.08, 95% confidence interval 1.09–4.00) among women who stopped working night shifts after the first pregnancy trimester (N=3094). ' ' CONCLUSION ': 'Overall, our results do not support night work during pregnancy as a risk factor for severe PPD among hospital employees. However, we observed a 2-fold increased risk of PPD among women who stopped working night shifts after the first pregnancy trimester. This may reflect the influence of the healthy worker survivor effect and warrants further attention.
Keywords: cohort study; depression; depressive disorder; doctor; healthy worker effect; night work; nurse; postpartum depression; pregnancy; register-based cohort study; shift work; shift worker